Personal Data Protection in Russia and the Risks of Malicious Use of Artificial Intelligence Technologies: New Challenges to Psychological Security - Pashentsev, Evgeny; Blekanov, Ivan; Chernobrivchenko, Anastasia (Sociološki pregled, 2023)
The paper focuses on the relationship between personal data protection and technologies of artificial intelligence (AI) in the context of threats to the psychological security of society on the case study of the Russian Federation. The research identifies existing and prospective risks of malicious use of AI involving personal data to affect the psyche of people. The paper examines the possibilities of a comprehensive response to new threats of psychological security. The research methodology is based on the systemic approach, dialectical method and comparative analysis of the national and international components of the research problem.